PKMS Peningkatan Keterampilan Kelompok Ibu-Ibu Orangtua Murid SD Muhammadiyah Pulo Brayan - Zubaidah Hanum; Iswandi Idris; Neni Triastuti; Ruri Aditya Sari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The target partners of PKMS are community groups with non-productive types of partners, namely parents of first grade elementary school students led by Mrs. Dian Novita with a total of 40 parents. The problem of partners feeling bored, anxious about the covid-19 pandemic situation and has not found products that can be sold during the covid-19 pandemic and how to market them. The training is carried out both in theory and practice with resource persons who are experts in their fields through questions and answers, discussions and exercises. PKMS success indicators are publications in national journals, media mass publications, video implementation of activities, increasing partner empowerment in the form of increasing knowledge, skills and income. The partner location is 10 km from Politeknik LP3I Medan, namely on Jalan Cemara Gang Nangka Pulo Brayan. The results of PKMS show an increase in knowledge and skills, partners. Partners can minimize boredom by participating in motivational training, business knowledge, training to make cloth masks and using social media to sell skills or become resellers